2001
DOI: 10.1103/physrevlett.86.4001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Reorientation in Collisions ofOH+Ar

Abstract: Orientational effects in rotationally elastic collisions of OH with Ar were studied in a crossed molecular beam setup. A static electric field was applied to orient the molecules before the collision. After the collision the orientation was measured by using a narrow-band laser system to probe the Stark-split states corresponding to different orientations. Differential and integral cross sections for reorientation of the molecular axis have been determined as a function of the initial orientation. The cross se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…They found an intriguing angular, oscillating dependence of the orientation as a function of scattering angle. Van Beck et al 9 observed orientational effects in OH͑X 2 ⌸͒ -Ar rotationally inelastic collisions in a crossed beam experiment, and differential and integral cross sections for reorientation of the molecular axis were determined as a function of the initial orientation. Stolte and co-workers 10,11 investigated the steric asymmetry in rotationally inelastic collisions of NO͑X 2 ⌸͒ with several collision partners.…”
Section: Introductionmentioning
confidence: 99%
“…They found an intriguing angular, oscillating dependence of the orientation as a function of scattering angle. Van Beck et al 9 observed orientational effects in OH͑X 2 ⌸͒ -Ar rotationally inelastic collisions in a crossed beam experiment, and differential and integral cross sections for reorientation of the molecular axis were determined as a function of the initial orientation. Stolte and co-workers 10,11 investigated the steric asymmetry in rotationally inelastic collisions of NO͑X 2 ⌸͒ with several collision partners.…”
Section: Introductionmentioning
confidence: 99%
“…31 The collision induced reorientation of the OH radicals was measured by probing the Stark-split states of the products corresponding to different orientations. 32 Under thermal bulk conditions, the evolution of oriented or aligned OH (X 2 P) radicals was studied in collisions with argon by polarization spectroscopy. 33,34 Detailed information on the OH(X 2 P)-Ar PES has also been obtained from spectroscopic study of the bound states of the OH-Ar van der Waals complex.…”
Section: Introductionmentioning
confidence: 99%
“…Further state selection can be achieved by optical preparation of a single quantum state or by purification of the beam with the use of electrostatic or magnetic multipole fields (2,3 ). These methods allow the orientation of the molecules to be controlled before the collision (8,9 ) and the orientation of the scattered products can be measured (10 ).…”
mentioning
confidence: 99%